IMPLEMENTASI TEKNOLOGI DALAM MANAJEMEN KELAS DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL KAHFI KABUPATEN SAROLANGUN - Thoriq Kurniawan; Samsu; Edi Kusnadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze in-depth the implementation of technology in classroom management at SMP IT Al Kahfi Sarolangun and evaluate its effectiveness in supporting the learning process. Furthermore, this study also identifies various supporting and inhibiting factors that influence the optimal implementation of this technology. The results indicate that the use of technology, such as digital devices, online learning platforms, and interactive media, can improve the quality of interactions between teachers and students, strengthen student engagement, and increase the efficiency of overall classroom management. Technology also makes it easier for teachers to assess, document, and monitor student learning progress. However, this study identified several obstacles that hinder the optimal implementation of technology. These obstacles include limited teacher competency in utilizing technology effectively, a lack of specialized training, and the unequal distribution of technological facilities and infrastructure, such as internet connections and supporting devices. Supporting factors identified include support from school policies, the readiness of some teachers to adapt, and student enthusiasm for using technology in learning. Thus, this study confirms that the use of technology in classroom management has significant potential to improve the quality of learning, but requires serious attention to improving teacher capacity and strengthening supporting infrastructure.